Lasem: Harmoni dan Kontestasi Masyarakat Bineka - Hadi, Syamsul (Islam Nusantara: Journal for the Study of Islamic History and Culture, 2020)
This article aims to explain how the contestation of social spaces in the lives of the plural society at Lasem it processes dynamically. It is a pattern of space contestation that leads to the affirmation and strengthening of identity or a pattern that leads to the fusion of identities. As a consequence, the first pattern creates social friction or conflict. On the contrary, the second pattern is directed towards acculturation and assimilation of culture which can strengthen social harmony. The important finding of this research is that it can be known the real issue, so that problems related to all parties can be found a solution as well as a resolution. This research also proves that social mechanism preparedness is considered urgent to prevent negative excesses (negative things) from the space contestation. So the space contestation that occurs dynamically proves that the plural society in Lasem has found a valuable experience, namely social resilience in facing all possible emergence of social disintegration.Keywords: contestation, space, social mechanisms and an plural society REFERENCE: Abercrombie, Nicholas, at.all., 2010. Kamus Sosiologi, Terj. Dwi Agus M. Yogyakarta: Pustaka Pelajar. Adhyanggono, GM. ad.all., 2009. Budaya Tionghoa Lasem Dalam Peta Tata Pemukiman, Tradisi, Peran Dan Relasi Gender, dalam Angelina Ika Rahutami (Peny.), â€Kekuatan Lokal Sebagai Roh Pembangunan Jawa Tengahâ€, Semarang: UNIKA Soegijapranata. Amirudin, 2017. Multikulturalisme dalam Produksi Budaya Seni Batik di Lasem, dalam; â€60 Tahun Antropologi Indonesia; Refleksi Kontribusi Antropologi untuk Indonesiaâ€, Jakarta; Pusat Kajian Antropologi, Departemen Antropologi FISIP UI, 2017. Atabik, Ahmad, 2016. Percampuran Budaya Jawa dan Cina: Harmoni dan Toleransi Beragama Masyarakat Lasem, Jurnal: Sabda, Volume 11, Tahun 2016, pp. 1â€“11. Azra, Azyumardi, 2011. Nasionalisme, Etnisitas, Dan Agama di Indonesia: Perspektif Islam Dan Ketahanan Budaya, dalam Thung Ju Lan dan M. Azzam Manan (Ed.), â€Nasionalisme Dan Ketahanan Budaya di Indonesiaâ€, Jakarta: LIPI & Yayasan Obor Indonesia. BPS. 2012. Data Monografi Kecamatan Lasem Semester II Tahun 2012, Rembang: Pemkab. Rembang. BPS. 2017. Data UPT Pendidikan Kabupaten Rembang Tahun 2017, Rembang: Pemkab. Rembang. BPS Rembang, 2017. Lasem Dalam Angka Tahun 2017, Rembang: Pemkab. Rembang. BPS Rembang, 2018. Lasem Dalam Angka Tahun 2018, Rembang: Pemkab. Rembang. Daradjati, 2013. Geger Pacinan 1740â€“1743: Persekutuan Tionghoa â€“ Jawa Melawan VOC, Jakarta: Kompas. Hardiman, F. Budi, 2002 â€œBelajar dari Politik Multikulturalismeâ€, pengantar Will Kymlicka, â€Kewargaan Kulturalâ€, Jakarta: LP3ES, 2002. Hartono, Samuel & Handinoto, Lasem: Kota Kuno Di Pantai Utara Jawa Yang Bernuasa Cina, artikel dalam: http://fportfolio. petra.ac.id/user_files/81-005/LASEM.pdf, diunduh pada tanggal 02 Agustus 2018, pukul: 14.23 wib. Hefner, Robert, W., 2001, The Politics of Multiculturalism: Pluralism and Citizenship in Malaysia, Singapore and Indonesia, Honolulu: University of Hawai Press. Jary, David & Jary, Yulia, 1991. Collins Dictionary of Sociology, London: Harper Collins Publishers. Khamzah, R.P. 1858. Cerita (Sejarah) Lasem, Katurun/Kajiplak Dening R. Panji Karsono (1920), dalam buku Badra Santi, Rumpakanipun Mpu Santribadra Nurhajarini, Dwi Ratna, ad.all. 2015. Akulturasi Lintas Zaman di Lasem: Perspektif Sejarah dan Budaya (Kurun Niaga â€“ Sekarang), Yogyakarta: BPNB-Yogyakarta. Onghokham, Anti Cina, Kapitalisme Cina dan Gerakan Cina, Jakarta: Komunitas Bambu, 2008. Parekh, Bhikhu, 2012. Rethingking Multiculturalism: Keberagaman Budaya dan Teori Politik, diterjemahkan dari â€œRethingking Multiculturalism, Cuktural Diversity dan Political Theoryâ€, Yogyakarta: Kanisius. Pemkab. Rembang, 2012. Monografi Kecamatan Lasem Tahun 2012. Poloma, Margaret M. 2010. Sosiologi Konterporer, Jakarta: Rajawali Press. Purdey, Jemma, 2013. Kekerasan Anti Tionghoa Di Indonesia 1996â€“1999, Denpasar: Pustaka Larasan. Putra. Ade Yustirandy dan Sartini, 2016. Batik Lasem Sebagai Simbul Akulturasi Nilai-nilai Budaya Jawa-Cina, dalam; Jurnal Jantra Vol. 11, No. 2, Desember 2016. Ritzer, George & Goodman, Douglas J., 2011. Teori Sosiologi Modern, Jakarta: Prenada Media. Saifullah, Ahmad 2008. Makna Spiritual Arsitektur Masjid, paparan makalah SITI Angkatan Ke-4, dipresentasikan pada Kamis, 17 Juli 2008, Tidak Diterbitkan. Slattery, Martin, 2003. Key Ideas in Sociology, Delta Place Cheltenham: Nelson Thomas Ltd. Soekanto, Soejono. 1985. Karifan Masyarakat Dalam Penegolaan Kseserasian Sosial Ditinjau Dari Segi Hukum, dalam Majalah Bulanan Tahun VII, edisi No. 11/Agustus 1985, pp. 824-830. Suaedy, Ahmad, 2018. Gus Dur, Islam Nusantara, dan Kewarganegaraan Bineka: Penyelesaian Konflik Aceh dan Papua 1999â€“2001, Jakarta: Gramedia Pustaka Utama. Suryadinata, Leo, 2003. Kebijakan Negara Indonesia terhadap Etnik Tionghoa: Dari Asimilasi ke Multikulturalismeâ€, Jurnal Antropologi Indonesia, Nomor: 71, Tahun 2003. Suryadinata, Leo, 2010. Akhirya Diakui Agama Konghucu dan Agama Budha di Pasca-Suharto, dalam, â€Setelah Air Mata Keringâ€ (Ed. I. Wibowo & Thung Ju Lan), Jakarta: Gramedia. Slattery, Martin, 2003. Key Ideas in Sociology, Delta Place Cheltenham: Nelson Thomas Ltd. Tan, Charlene, 2014. Educative Tradition and Islamic Schools in Indonesia, Nanyang Technological University, Singapore. Journal of Arabic and Islamic Studies-14 (2014). Tilaar, H.A.R. 2007. Mengindonesia: Etnisitas dan Identitas Bangsa Indonesia, Jakarta: Rineka Cipta. Tim Peneliti, â€Laporan Survei Nasionalâ€: Kerjasama Wahid Foundation dengan Lembaga Survei Indonesia dan UN Women, Januari 2018. Turner, Jonathan H. dan Alexandra Maryanski, 2010. Fungsionalisme, Yogyakarta: Pustaka Pelajar. Unjiya, M. Akrom, 2008. â€œLasem Negeri Dampo Awang: Sejarah Yang Terlupakanâ€œ, Yogyakarta: Fokmas, Veeger, K.J., 1985. Realitas Sosial: Refleksi Filsafat Sosial Atas Hubungan Individu-Masyarakat Dalam Cakrawala Sejarah Sosiologi, Jakarta: Gramedia. Wallace, Ruth A. dan Wolf, Alison, 2006. Contemporary Sociological Theory: Expanding The Classical Tradition, -6th ed., Pearson Education, Inc., Upper Saddle River, New Jersey. Wiroutomo, Paulus, 2012. Integrasi Sosial Masyarakat Indonesia: Teori dan Konsep, dalam Paulus Wiroutomo, ad.all., â€Sistem Sosial Indonesiaâ€, Jakarta: UI Press & Lab-Sosio. Sumber Internet Surat Kabar Harian â€œKompasâ€, edisi; 15 Pebruari 2014. Surat Kabar Harian â€œSuara Merdekaâ€, edisi: 23 Oktober 2019. "Said Aqil Singgung Sentimen Agama dan 212 di Depan Anies", sumber; https://www.cnnindo nesia.com/nasional/20191022212949-20-441966/said-aqil-sing gung-sentimen-agama-dan-212-di-depan-anies, diunduh pada tanggal 23 Oktober 2019. Pukul:07.43 wib.